2013
DOI: 10.1111/joss.12070
|View full text |Cite
|
Sign up to set email alerts
|

The Comfort Dimension; a Review of Perception in Clothing

Abstract: For a clothing system, comfort is a fundamental necessity. In this paper, basic definitions and elements of clothing comfort and the general research trends were reviewed. In particular, understanding comfort of textile materials, its relevance to clothing choice and some assessment methods have been discussed. The impact of fabric and clothing attributes on clothing comfort was explored. Psychological, physical and physiological perceptions of clothing comfort were reviewed, including subjective and objective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
89
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(91 citation statements)
references
References 125 publications
(236 reference statements)
0
89
0
2
Order By: Relevance
“…Still it is not intended to be a comprehensive review of the topics, as there are, nonetheless, books 2,5 6 and a few published articles 1,[14][15][16] for that. In the discussions below, to maintain focus on the targeted issues, even though there may be various improved forms of the original theories, we only use the one sophisticated enough, not necessarily the most updated/accurate, to facilitate our analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Still it is not intended to be a comprehensive review of the topics, as there are, nonetheless, books 2,5 6 and a few published articles 1,[14][15][16] for that. In the discussions below, to maintain focus on the targeted issues, even though there may be various improved forms of the original theories, we only use the one sophisticated enough, not necessarily the most updated/accurate, to facilitate our analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Otherwise, some authors analyzes the satisfaction with clothes from the emotional perspective, mainly related to body image, social aspects, and self-realization (Kamalha et al, 2013;Norton et al, 2013;Rudd & Lennon, 2000;Tiggemann, 2012;Tsaousi & Brewis, 2013;Chattaraman & Rudd, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In a more sociological approach, body image, personality, values or beliefs, personal interests and awareness among others interfere in comfort perception. Besides, garment attributes like style, texture, esthetics , fashion, suitability, design and color influences the comfort perception (Kamalha et al, 2013;Norton et al, 2013;Wages, 1974). It is important to maintain an affirmative self-image to perceived quality of life, as attractiveness has been viewed as a means to gain access to the power in a male world (Rudd & Lennon, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The goal of the majority of these works is the estimation of the magnitude of human sensations based on instrumental measures, with examples of such studies found in the field of fabric hand (Zheng et al 2004;Mazzuchetti et al 2008;Rombaldoni et al 2010;Jeguirim et al 2012;Wang et al 2012) and analysis of wet and clingy (Tang et al 2015) and comfort (Kamalha et al 2013) sensations, for instance. Our study also belongs to the sensory field but addresses the problem from a different angle.…”
Section: Introductionmentioning
confidence: 99%